Estimation of the incidence of disease with the use of prevalence data - Klaus Langohr (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 1999)
The incidence of a disease can be easily estimated from serial prevalence data. However, difficulties usually arise in the case of prevalence data measured only once. This paper presents and assesses various methods for estimating the incidence of a disease in the latter case. The focus is on how applicable the methods are to the estimation of the incidence of the HIV-epidemic in some parts of Africa where data from serial cross-sectional surveys are hard available.
Keywords: 519